The antagonistic effects of soil micro-organisms, isolated from the root region of clovers, on the colver root nodule bacteria (Rhizobium trifolii Dangeard) - Hattingh, M. J.(Marthinus Johannes) (Stellenbosch : Stellenbosch University, 2012)
Spine title: Microbial antagonism against Rhizobium trifolii.